PERANAN MAHASISWA KKN SEBAGAI WUJUD PENGABDIAN KEPADA MASYARAKAT DI DESA KAMELOH BARU - Sabarun (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2024)
This article discusses the activities carried out by KKN students, so that it aims to provide experience and as a learning process for students to explore village potentials that can be developed by the community. The method of implementing KKN at the location consists of survey activities, and planning additional activities besides the planned core activities. The Palangka Raya State Islamic Institute's Community Service Program is spread throughout the Central Kalimantan region. This Community Service was carried out from 15 August to 30 September 2023. This activity also received support from the local government and the village community. The KKN activities of the Palangka Raya State Islamic Institute are expected to provide benefits to the village community, especially those aimed at creating peace and improving the economy of the village community. Keywords: student role, Community service, a form of service.